Satisfaction of Pregnant Women when Checking Teeth at the Public Health Center - Ika Kusuma Wardani; Andi Istiqomah; Rindang Fitria Ulfa; Ambika Kurnia Mustikawati (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2022)
Background: Based on a preliminary study in the Tana Lili Public Health Center area, it was found that 11 pregnant (32.2%) had never had their teeth checked at the health center during pregnancy. Pregnant women do dental examinations at the health center or dentist if there are get toothache, cavities, bleeding gums, and others The aims of this study was to find out the description of pregnant satisfaction during dental check-ups at the health center towards the marketing mix. Methods: This research is a descriptive study with cross-sectional design. The sampling technique used purposive sampling by inclusion and exclusion criteria. The inclusion criteria in this study were pregnant women in the Tana Lili Public Health Center area who were willing to participate in this study. Exclusion criteria in this study were pregnant women who did not fill out the questionnaire completely. The number of samples in this study was 34 pregnant women. Results: Most of the pregnant women as many as 25 people (73.6%) were pregnant women who had a child. Most of the pregnant women were 17 people (50%) with high school education and the most occupations were housewives as many as 18 people (52.9%). Most pregnant women's husbands are self-employed as many as 15 people (44.1%). The highest family income is in the very high category, which is 13 people (38.2%). Pregnant women are satisfied with service products are 18 people (52.94%), price 23 people (67.65%), promotion 24 people (70.58%), people 22 (64.7%), process 23 people (67.65%), physical evidence 18 people (52.94%) and very satisfied with the place are 22 people (64.7%). Conclusion: Most pregnant women are satisfied with the product, price, promotion, people, process, physical evidence and are very satisfied with the places of the Tana Lili Public Health Center. Further research is needed with qualitative research to explore the reasons for pregnant women who are partially dissatisfied with promotion, people, and physical evidence so that public health center can improve their services.